If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -36 = x + -6x + -6 Reorder the terms: -36 = -6 + x + -6x Combine like terms: x + -6x = -5x -36 = -6 + -5x Solving -36 = -6 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -36 + 5x = -6 + -5x + 5x Combine like terms: -5x + 5x = 0 -36 + 5x = -6 + 0 -36 + 5x = -6 Add '36' to each side of the equation. -36 + 36 + 5x = -6 + 36 Combine like terms: -36 + 36 = 0 0 + 5x = -6 + 36 5x = -6 + 36 Combine like terms: -6 + 36 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 9x^2+4x^4-3x^2-x^4-6x^2= | | -7+4x=29 | | -6+2x=-30 | | -8(3b+4)+(25b-3)=0 | | 14/y=2/1/7 | | x-1+2x=-1 | | 132/22=n/17 | | 80=4x+2x+8 | | x/32=7/16 | | (4y+5)-(4+3y)=2 | | 5x-14=34+x | | 16x=-5 | | x^2+2=10-x^2 | | 4x^2y+5xy^2-8xy^2+5xy= | | 3(16)+2x-6= | | -2x(6x^4-x)= | | 2s+(6s+16)=-24 | | p=14a-11bfora | | p=14a-11b | | x+0.12688x=43472.6 | | -5(1-5x)=-4x-8x | | 2+(5b+2y/4)-(5b-8y/8b) | | ap-c=b | | 17x-7x=-8 | | 4t+4+5t-8t=6+6 | | 3(x-1)+2x+6=12 | | 3(256)+2x-6= | | (x-2/x^2-x-2)(3x-6/x-1) | | 4+3x7-6/2 | | 7/8*4/5 | | 25+25+25-25-25-25-25= | | e=rb |